Construction of brick wall & boundary wall for : 13 storied Brac University new campus building holding no. 224, Merul Badda ,Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and NS Construction Limited to construction of brick wall & boundary wall for : 13 storied Brac University new campus building project.